2020
DOI: 10.3390/ijms21103437
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Zinc Oxide Nanoparticles Disrupts Endothelial Tight and Adherens Junctions and Induces Pulmonary Inflammatory Cell Infiltration

Abstract: Zinc oxide nanoparticles (ZnONPs) are frequently encountered nanomaterials in our daily lives. Despite the benefits of ZnONPs in a variety of applications, many studies have shown potential health hazards of exposure to ZnONPs. We have shown that oropharyngeal aspiration of ZnONPs in mice increases lung inflammation. However, the detailed mechanisms underlying pulmonary inflammatory cell infiltration remain to be elucidated. Endothelium functions as a barrier between the blood stream and the blood vessel wall.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
(51 reference statements)
1
11
0
Order By: Relevance
“…Disconnection of VE-cadherin-βcatenin is widely present in the endothelium during pro-inflammatory conditions (Barbieri et al, 2008;Taha et al, 2014). Our results showed (Chen et al, 2020). All these results verified that the VE-cadherin-βcatenin complex forms the molecular basis of tight junctions (Cao & Schnittler, 2019).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Disconnection of VE-cadherin-βcatenin is widely present in the endothelium during pro-inflammatory conditions (Barbieri et al, 2008;Taha et al, 2014). Our results showed (Chen et al, 2020). All these results verified that the VE-cadherin-βcatenin complex forms the molecular basis of tight junctions (Cao & Schnittler, 2019).…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have demonstrated that the cytoplasmic domain of VE-cadherin is combined with β-catenin and that VE-cadherin dynamics at the plasma membrane is essential for modulating endothelial adhesion. The dissociation of the VE-cadherin-β-catenin complex during inflammation results in cytoplasmic accumulation of 70-95 kDa fragments of VE-cadherin and βcatenin, thus initiating cell adhesion (Chen et al, 2020;Schäfer et al, 2003;Su & Kowalczyk, 2017;Vargas et al, 2016). Our previous studies have shown that the expressions of VE-cadherin at 130 kDa and βcatenin at 92 kDa were not altered during monocyte transendothelial migration (Deng et al, 2017); however, it is still unknown whether the interaction between VE-cadherin and cytoplasmic β-catenin is affected during the cell-cell adhesion induced by pro-inflammatory cytokines.…”
mentioning
confidence: 99%
“…Figure 3 shows the biological distribution of the NPs in circulation. ZnO NPs can lead to the production of ROS, which cause significant loss of cell adhesion, mitochondrial dysfunction, DNA damage, and functional damage in ECs (Chen et al, 2020; Giordo, Nasrallah, Al‐Jamal, Paliogiannis, & Pintus, 2020; Poier et al, 2020). Some studies have shown that the cytotoxicity of ZnO NPs is mainly caused by the potential change caused by the release of zinc ions, followed by an increase in ROS, leading to cell death by apoptosis and necrosis (Panda et al, 2017; Venkatasubbu, Baskar, Anusuya, Seshan, & Chelliah, 2016).…”
Section: Toxicity Of Metal Oxide Nanoparticles To Vascular Endotheliamentioning
confidence: 99%
“…As is shown in Figure 3, ZnO NPs decrease the EC viability in a dose‐ and time‐dependent manner and induce apoptosis and necrosis. ZnO NPs have also been reported to disrupt the endothelial barrier, impair the integrity and stability of the junction network, cause inflammatory cell infiltration, and even induce atherosclerosis (Chen et al, 2020; Yan et al, 2017).…”
Section: Toxicity Of Metal Oxide Nanoparticles To Vascular Endotheliamentioning
confidence: 99%
“…There are extensive studies which investigated the toxicity of metal particles to ECs (C. M. Chen et al, 2020; Duan et al, 2014; Gholinejad et al, 2019; Gonzalez‐Palomo et al, 2021; Guo et al, 2018; Guo et al, 2016; Khan et al, 2019; Lee et al, 2019; Liang et al, 2020; Liang et al, 2016; X. Liu et al, 2021; Poier et al, 2020; Shi et al, 2014; D. P. Wang et al, 2020; W. Wang et al, 2018; Yan et al, 2020; Zeng et al, 2018). Numerous studies have reported that silica NPs (Si NPs) can induced apoptosis, autophagy, inflammation and oxidative stress through multiple signaling pathways, which in turn trigger vascular endothelial cell injury (Duan et al, 2014; Guo et al, 2018; Guo et al, 2016; Lee et al, 2019; X. Liu et al, 2021; D. P. Wang et al, 2020; W. Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%